Enhanced CO2 uptake by intramolecular proton transfer reactions in amino-functionalized pyridine-based ILs. Issue 44 (18th April 2017) - Pan, Mingguang; Vijayaraghavan, R.; Zhou, Fengling; Kar, Mega; Li, Haoran; Wang, Congmin; MacFarlane, Douglas R.
Abstract : This work presents a new strategy for the promotion of CO2 uptake by an intramolecular proton transfer reaction in amino functionalized hydroxypyridine based anions. Abstract : This work presents a new strategy for the promotion of CO2 uptake by an intramolecular proton transfer reaction in amino functionalized hydroxypyridine based anions.